Controllability and Observability Analysis of DC Motor System and a Design of FLC-Based Speed Control Algorithm - Iswanto Suwarno; Yaya Finayani; Robbi Rahim; Jassim Alhamid; Ahmed Ramadhan Al-Obaidi (Journal of Robotics and Control (JRC), 2022)
DC motor is an electrical motor widely used for industrial applications, mostly to support production processes. It is known for its flexibility and operational-friendly characteristics. However, the speed of the DC motor needs to be controlled to have desired speed performance or transient response, especially when it is loaded. This paper aims to design a DC motor model and its speed controller. First, the state space representation of a DC motor was modeled. Then, the controllability and observability were analyzed. The transfer function was made based on the model after the model was ensured to be fully controllable and observable. Therefore, a fuzzy logic controller is employed as its speed controller. Fuzzy logic controller provides the best system performance among other algorithms; the overshoot was successfully eliminated, rise time was improved, and the steady-state error was minimized. The proposed control algorithm showed that the speed controller of the DC motor, which was designed based on the fuzzy logic controller, could quickly control the speed of the DC motor. The detail of resulted system performance was 2.427 seconds of rising time, 11 seconds of settling time, and only required 12 seconds to reach the steady state. These results were proved faster and better than the system performance of PI and PID controllers.